Analisis Pengaruh Word Of Mouth Dan Customer Trust terhadap Purchase Intention pada Perusahaan Ud Sumber Alam - Hugo, Albert; Sudyasjayanti, Christina (PERFORMA, 2023)
UD Sumber Alam is a business that focuses on selling rice, onions and beans. UD Sumber Alam was founded in 2019. Sales carried out by UD Sumber Alam were carried out on a retail and wholesale scale and at the beginning of its establishment, sales were actually carried out on a wholesale or party scale, but in its development, retail or retail sales began. This business is a business that was built traditionally and experienced challenges, especially in terms of increasing the number of consumers. Since its establishment until now, it has been found that there is no significant growth in the number of consumers from year to year. Based on observations, it is known that the difficulty in increasing the number of consumers is caused by the lack of customer trust in UD Sumber Alam and the lack of word of mouth circulation that supports UD Sumber Alam. Customer trust is difficult to build, especially for buyers who make transactions in wholesale quantities. The circulating word of mouth is still not able to help UD Sumber Alam in developing the number of consumers because the circulation of word of mouth is only limited to the environment close to consumers. Based on the description of previous research, it was found that customer trust and word of mouth played a very important role in influencing purchase intention, therefore in this study it was observed how the influence of word of mouth and customer trust on purchase intention. In an effort to obtain research data, in this study, questionnaires were distributed to research respondents as many as 78 respondents. Based on the results of the distribution of the questionnaire obtained 78 responses. The data obtained were processed using multiple linear regression method. The results showed that word of mouth and customer trust had an effect on purchase intention. The form of influence that occurs between the variable word of mouth and customer trust is a positive influence. The results of the research obtained further support the results of the previously disclosed research.